A REVIEW: A ROLE OF CAPSAICIN TO REGULATING T2R AND TRPV1 AND ITS ASSOCIATION IN CANCER DEVELOPMENT - Faruk Rokhman Ardi Putra; Anis Irmawati (Universitas Airlangga, 2023)
Cancer is one of the leading causes of death in the world. It is estimated that this disease has caused 10 million deaths. The cause of the development of cells into cancer is still a mystery until we know that cancer is a disease that occurs due to an imbalance of molecular genes and cell receptors. Bitter taste receptors (T2R) are known to be expressed outside the taste buds and detect the perception of a bitter taste. These receptors are known to be involved in the mechanism of cancer cell development. Capsaicin is involved in a wide variety of genes that regulate the life cycle and growth of cancer cells. The activity of Capsaicin in inhibiting cell growth can be observed through various target genes, such as oncogene signaling pathways and tumor-suppressor genes. The systematics in this article is carried out using four electronic databases, namely Google Scholar, PubMed, ResearchGate, and NCBI. The keywords used are